O ato de estudar: a escola e o ensino aprendizagem na percepção de alunos do 1º ano do ensino médio em uma escola pública de Castanhal/PA - SOUSA, Renata Gabriele Ramos de (2019)
School education plays a fundamental role in the development of the human being, and through social, political and cultural changes, educational models are modified in order to adapt to their current situation. Considering this, the present field research discusses the perception of the students of the 1st high school of a public school of Castanhal-PA about the act of studying, the school and the process of teaching and learning. It analyzes through the collected data the perception that the students have about their schooling, considering the reality of the school in question as well as the participant context. The study is based on the qualitative approach of research, being oriented through the principles and procedures of the field research, of the descriptive type. Structured interview technique is used for data collection. The object of study is analyzed with reference to the theoretical productions that discuss the educational field, with emphasis on the works of: Brandão (2001), Freire (1991) and Nóvoa (1995), as well as others related to this field of study. The results indicate that according to the students' perception, which school is considered a place for learning, being a main reference in the search for new knowledge of the youngsters in question. Moreover, for many, studies mean the guarantee of a better future. Another important issue is the need for a school transformation in order to promote an education that corresponds to current demands, as well as the reality investigated is contextualized.